Material behaviour in micropolar fluid of Brownian motion over a stretchable disk with application of thermophoretic forces and diffusion-thermo (Journal of Naval Architecture and Marine Engineering, 2021)
To study the material behavior of axisymmetric flow in micropolar fluid for heat and mass exchange over a stretchable disk placed in porous medium taking into account the effect of heat generation, diffusion thermo, Brownian motion and thermophoretic effect. A suitable similarity transformations is adapted to convert the governing PDEs to non-dimensional form. A well-tested, numerically stable MATLAB code in connection with Bvp4c is employed for the conservation of equations. The noticeable features of the relevant parameters on micropolar fluid flow for axial velocity, radial velocity, micro-rotation, temperature and species concentrations profiles are accentuated on the plots using MATLAB. It is found that angular velocity is enhanced for augmented values of micropolar parameter. Moreover, due the effect of thermophoretic force, the thickness of thermal and concentration boundary layer are enhanced. In addition, thermal diffusion becomes more due to the increase in the vortex viscosity of the fluid, and an amplified thermal and molar concentration boundary layer thicknesses can be found.  This study incorporates numerous engineering applications on rotating machineries, spin-coating, centrifugal pumps, computer storage devices, chemical engineering and different aerodynamic issues. Also, this analysis signifies great impact on biomechanics and stenosis related issue in medical sciences.